Exploring the potential of assessment efficacy in sports coaching - Hay, P.; Dickens, S.; Crudgington, B.; Engstrom, C. (International Journal of Sports Science and Coaching, 2012)
The role of learning across the cognitive, psychomotor and affective domains in both coach development and in the practice of coaching has been increasingly recognised in the field of sports coaching. A burgeoning body of literature focused on coach pedagogy has reflected this emerging awareness of the centrality of definable forms of learning and has presented a better balance to the already well-established body of literature devoted to the content of coaching and sports performance. This article draws on Bernstein's three message systems to highlight the absence of reference to the inter-related message system of assessment within coaching development and accreditation as well as the practice of coaching itself. In so doing, this article outlines four conditions of assessment efficacy (learning-oriented, authentic, valid and socially just) and explores the potential of assessment to optimise the learning and accreditation outcomes of coach development programs, and to enhance the learning and performance outcomes of the athletes they work with.